Sustainability Performance Determinants With Investment Opportunity As Moderation - WERASTUTI, Desak Nyoman Sri (International Journal of Environmental, Sustainability, and Social Science, 2022)
This study aims to determine the effect of public ownership and public ownership on sustainability performance with the Investment Opportunity Set (IOS) as a moderating variable. This type of research is quantitative associative using secondary data taken from the IDX website. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange from 2015 to the end of 2019. The sample selection procedure in this study used the purposive sampling method; only 87 company data met the criteria. The results of this study Public Ownership have a significant effect on sustainability performance; there is an effect of public ownership on sustainability performance. The IOS can moderate the influence of Public Ownership on Sustainability performance.